Exploring the Potential of Renewable Energy in Today's Engineering Development - Wang Joshua; Uwe Barroso; Matteson Niva (Yayasan Adra Karima Hubbi, 2024)
The utilization of renewable energy is becoming increasingly important in today's engineering development to address environmental challenges and energy sustainability. However, the full potential of renewable energy sources has yet to be fully explored. This study aims to explore the potential of renewable energy in the context of contemporary engineering development with a focus on identifying renewable energy sources that can be optimized and integrated in engineering infrastructure. The research methods used include literature survey, data analysis, and modeling to evaluate various renewable energy sources that can be applied in engineering development. An interdisciplinary approach was used to gain a holistic understanding of the potential and limitations of each energy source. The study identified that renewable energy, such as solar, wind, hydro, and biomass, has great potential in providing clean and sustainable energy sources for today's engineering development. In-depth analysis also shows that the integration of renewable energy systems can reduce dependence on fossil fuels and reduce greenhouse gas emissions. By tapping into the potential of renewable energy, today's engineering developments can become more sustainable and environmentally friendly. The integration of renewable energy in engineering infrastructure not only reduces negative environmental impacts but also creates new opportunities for innovation and sustainable economic growth.